‫واقع‬‫ تطبيق‬ ‫المبادئ‬ الاساسية‬ ‫للرقابة‬ ‫المصرفية‬ ‫الفعالة‬ ‫الصادرة‬ ‫عن‬ ‫لجنة‬ بازل‬ ‫في ‬‫البنوك‬ ‫التجارية‬ ‫الجزائرية - محمد ‫دي‬‫ــدي‬ ‫ ‬; ‫عصــام‫ فرنـ‬‫ــانــة‬‬ (My University, 2018)
In this paper, we discuss banking supervision according to the standards and principles set by the BALE Committee for Supervision. 89And the commitment of Algerian banks to implement these principles. The primary purpose of banking supervision is to ensure the existence of a sound banking system capable of responding to economic development, and the existence of the principles and standards of the BALE Committee ensures the existence of banking supervision to achieve this objective within the framework of regulations and laws. Algeria is one of the countries that made the principles of the BALE Committee a standard for the development of Algerian banking supervision and the formation of a solid system to deal with the problems and crisis. .................................................................. ونتناول في هذا البحث الرقابة المصرفية في ضوء المعايير والمبادئ التي وضعتها لجنة للإشراف. 89والتزام البنوك الجزائرية بتنفيذ هذه المبادئ. الالغرض الأساسي من الإشراف المصرفي هو ضمان وجود - نظام مصرفي سليم قادر على الاستجابة للتنمية الاقتصادية. ووجود مبادئ ومعايير لجنة بال ويضمن وجود الرقابة المصرفية لتحقيق هذا الهدف في إطار اللوائح والقوانين. الجزائر من الدول التي صنعت مبادئ الـ BALE لجنة معيار تطوير الرقابة المصرفية الجزائرية وتشكيل نظام متين للتعامل مع المشاكل والأزمات.
‬